Islamic Banking System in Nigeria: Challenges and Gains from Its Operation - Olaoye, Ayoola Azeez; Adeniyi, Ayodeji Lasunkanmi; Bello, Wasiu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
In contrast to traditional banking systems, this study assesses the challenges facing the Islamic banking system and the gains accrued to its operation from the point of view of the Nigerian economy. The staff and stakeholders of the selected Islamic banks in Nigeria were the focus of structured questionnaires and interviews conducted as part of a mixed-methods research approach. Secondary data came from industry reports, academic journals, and government regulations. A sample of 450 staff from the banks was selected using a stratified sampling method. The study used descriptive and inferential statistical techniques to analyze the data. Findings discovered inadequate public knowledge, a lack of Sharia-compliant investment opportunities, and regulatory shortcomings are some of the main issues noted. Despite this, Islamic banks play a vital role in Nigeria’s efforts to reduce poverty, promote ethical investing, and promote financial inclusion. The results also show that Islamic banks are superior at managing credit risk. These results provide policymakers and Islamic financial institutions with doable suggestions for raising public awareness, creating thorough regulatory frameworks, and extending financial inclusion initiatives.